On the deformation of transversely isotropic porous elastic circular cylinder - Ghiba, I.-D. (Archives of Mechanics, 2009)
In this paper we study the deformation of right circular cylinders filled by a linear transversely isotropic porous material. We construct a solution of the relaxed Saint–Venant’s problem using the results established for anisotropic porous cylinders. Firstly, we decompose the relaxed Saint–Venant’s problem into two problems: extension–bending–torsion problem and flexure problem. Then, for each of them we give the exact expressions of the solutions.